How to Do Things with Things, or, Are Blue Beads Good to Think? - Anna Agbe-Davies (Semiotic Review, 2016)
Archaeologists are accustomed to thinking of artifacts as signs to be read.  Specifically, some artifacts are treated as symbols, conventional and law-like signs of past traditions and beliefs.  This matters for historical archaeologists because we approach these symbolic meanings of artifacts through texts and ethnography.  Here, I lay out a framework, grounded in Peircian principles that prioritizes the material qualities of signs and argue that it is well suited to an historical archaeology that seeks to liberate interpretations from the tyranny of the text and a bias towards symbolic interpretations.  African diaspora archaeology in particular places great value on survivals, markers, etc., yet pays less attention how these traditions operated within specific cultural contexts.  This paper examines beads recovered from slave quarters occupied in the 18th and 19th centuries and explores their meanings—for the people who owned them and the people who find them.